Dynamic resource adaptation method for airborne network based on multi-objective optimisation. Issue 4 (18th April 2020) - Guo, Jin; Zhang, Shengbing
Aiming at the problem that the existing methods have low resource utilisation, low task submission success rate, high overhead and high consumption in the process of airborne network resource adaptation, a dynamic resource allocation method based on multi-objective optimisation for airborne network is proposed. Taking the RAGE delay of the airborne network system model as the objective function, the problem is transformed into the graph dyeing problem. By constructing the dynamic resource migration model on the airborne network server and the application-aware dynamic resource migration model, the average delay in the dynamic resource allocation process of the airborne network can be achieved. The speech completed the key technical analysis of the dynamic resource adaptation of the airborne network. The experimental results show that the method overcomes the shortcomings of the existing methods, improves resource utilisation, task submission success rate and deadline satisfaction rate, reduces system overhead and improves user experience.